Climate Change, Child Health and Children’s Rights: From Inequality to Inequity - Reali, Laura; De Guchtenaere, Ann (Belgian Journal of Paediatrics, 2025)
Climate change is now recognized as the most significant global threat to child health and a major driver of inequity. The UNICEF Children’s Climate Risk Index estimates that around one billion children are currently exposed to extremely high levels of climate and environmental risk, including heatwaves, air pollution, flooding, water scarcity, and vector-borne diseases. Children are biologically, developmentally, and socially more vulnerable than adults, and they will live longer into a warming world, accumulating a greater lifetime burden of exposure. At the same time, the countries where children are most at risk contribute only a small fraction of global greenhouse gas emissions, while high-emitting countries experience comparatively lower vulnerability. This mismatch between responsibility and impact exemplifies climate-related inequity and intergenerational injustice. The 2025 Lancet Countdown confirms that children are increasingly exposed to extreme heat, air pollution, food insecurity, and climate-sensitive infectious diseases, with impacts that disproportionately affect the most vulnerable populations. These are not merely inequalities but structural inequities—avoidable and unjust differences arising from policy choices, governance gaps, and insufficient protection of children’s rights. This narrative review synthesizes evidence on: [1] the dynamics of the climate crisis and its intersection with environmental pollution; [2] health effects across the paediatric life course; [3] mechanisms underlying children’s unique vulnerability; and [4] the ways in which climate change undermines the rights set out in the UN Convention on the Rights of the Child, transforming inequalities into structural inequities. Finally, it outlines implications for paediatric practice, health systems, and climate governance, arguing that climate action must be explicitly child-centred and equity-oriented.